Peran orang tua dalam mendukung kesuksesan anak - Zulfa, Divana Indana (Maliki Interdisciplinary Journal, 2024)
The role of parents is crucial in supporting children’s educational and socio-emotional development. Parents’ active involvement in their children’s education can improve their children’s learning achievement, motivation and positive behavior. However, many parents still lack understanding of this role and often leave the responsibility of education entirely to the school. Factors affecting parental involvement include social barriers, limited time and money, and lack of caring. Parents can help their children develop better social-emotional skills by setting a good example, listening to their children, providing emotional support, teaching social skills, and providing praise and positive reinforcement. In addition, early character and value formation is very important, with parents providing proper education and being a good role model for their children.